Durability and mechanical performance of geopolymer mortar with partial replacement of fly ash by rice husk ash and variations in alkaline activator concentrations - Esamaddin M. Mulapeer; Ali H. Omar (Discover Civil Engineering)
Abstract This study investigates geopolymer mortar’s durability and mechanical performance with partial fly ash (FA) replacement by rice husk ash (RHA) and different alkaline concentrations. Forty-eight (48) mortar cubes were tested to assess compressive strength under different curing conditions and exposure to aggressive chemical environments. Two molar concentrations of sodium hydroxide (12 M and 14 M) were used as alkaline activators, along with sodium silicate, with FA replaced by RHA at varying levels (0%, 3%, 6%, 9%, 12%, and 15%). The results showed that increasing the RHA content improved the compressive strength, particularly at 28 days of ambient curing. However, the early-stage strength development (1-day heat curing) decreased as the RHA percentage increased, with reductions in strength gain observed at higher RHA levels. After 9 weeks of exposure to 5% sulfuric acid (H₂SO₄) and 5% sea salt (NaCl) concentration, durability tests showed that specimens with higher RHA content experienced more significant strength degradation. Notably, the NaCl resistance was more significant compared to H₂SO₄. In addition, increasing the molarity of NaOH from 12 to 14 M enhanced the compressive strength of the specimens by 11% and the acid resistance by 7%. The results indicate that while RHA can improve the mechanical properties of geopolymer mortars, its effect on durability in acidic environments requires careful study. This study concludes that RHA is a viable alternative to FA in geopolymer mortars, providing improved long-term strength, but its effect on chemical durability deserves further investigation for practical applications.